Kritis Syarat-Syarat Mufassir di Era Modern - Gunawan Hasibuan, Akmal Rizki; Insan Fadilah; Nasution, Khairiyah Asri; Hasibuan, Mutiah Rahmadhani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In the field of tafsir, individuals who analyze and explain the meaning of the Koran are referred to as mufassir. A Mufassir, or interpreter of the Koran, must adhere to the principle of prudence and avoid interpreting the text based on personal desires. Nevertheless, in conformity with the Divine Being who has disclosed the Qur'an. The interpreter's personality is a crucial factor in evaluating the quality of the interpretation output. As time advances, the field of interpretation should likewise evolve. Some contemporary scholars are hesitant to reinterpret the Qur'an due to the stringent standards set forth by classical scholars. This study employs qualitative research methodology, namely library research. The employed data collection strategy is a literature review method that utilizes diverse primary and secondary data sources. The research findings indicate that there are specific circumstances and criteria that must be met by an individual in order to be considered a mufassir, or an interpreter of the Al-Qur'an. The prerequisites, encompassing both physical and psychological aspects, along with scholastic criteria, aim to reinforce the outcomes of the interpretation that are unanimously agreed upon by the ulama and may be universally recognized by all segments of society.